2020
DOI: 10.3390/f11030339
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Araucaria angustifolia (Bertol.) Kuntze Timber Stocks With Liocourt’s Law in a Natural Forest in Southern Brazil

Abstract: This paper presents a simulation of the regulation of Araucaria angustifolia (Bertol.) Kuntze timber stocks using Liocourt’s law. Although this species is currently protected by law, recent government initiatives are being considered to propose sustainable forest management practices by selecting small rural properties in Southern Brazil. Here, we simulate the applicability of Liocourt’s law in a typical rural property, the size of which is approximately 85 ha. Forest inventory measurements were conducted by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…angustifolia is currently considered an endangered species at the international level and protected by a 20-year-old law in Brazil (BRASIL, 2001). Although the management of naturally forested areas of this species is mostly forbidden, recent initiatives have proposed that Mixed Ombrophilous Araucaria forests in Southern Brazil can be managed as sustainable sources of environmental, social and economic benefits (Longhi et al, 2018;Arnoni Costa et al, 2020). Clearly, however, much research is still needed to develop solid scientific data to support truly sustainable management strategies for such complex mixed stands subtropical forests, as models for low species diversity, temperate conifer stands, do not necessarily apply (Hess et al, 2018).…”
Section: Araucaria As a Viable Tropical Commercial Conifer Optionmentioning
confidence: 99%
“…angustifolia is currently considered an endangered species at the international level and protected by a 20-year-old law in Brazil (BRASIL, 2001). Although the management of naturally forested areas of this species is mostly forbidden, recent initiatives have proposed that Mixed Ombrophilous Araucaria forests in Southern Brazil can be managed as sustainable sources of environmental, social and economic benefits (Longhi et al, 2018;Arnoni Costa et al, 2020). Clearly, however, much research is still needed to develop solid scientific data to support truly sustainable management strategies for such complex mixed stands subtropical forests, as models for low species diversity, temperate conifer stands, do not necessarily apply (Hess et al, 2018).…”
Section: Araucaria As a Viable Tropical Commercial Conifer Optionmentioning
confidence: 99%
“…In any case, forest management yields better results if it favors the growth of young trees with growth potential that does not require large gaps in the canopy, assuring a higher incidence of light onto the lower canopy layer, keeping more trees growing in the forest. Likewise, regular management actions at reduced intervals allow the formation of healthy trees that are well-distributed on the dimension classes [47].…”
Section: Forest Management Scenariosmentioning
confidence: 99%
“…The panorama vitality loss of Araucaria crowns and the reduction of growth capacity, coupled with the lack of management protocols currently imposed by the legislation, induces illegal logging. Previous studies reported illegal logging as one of the significant environmental threats besides deforestation and land conversion [47].…”
Section: Insights Of Forest Management Initiativesmentioning
confidence: 99%
“…Parana pine (Araucaria angustifolia), a characteristic species of the Mixed Ombrophilous Forest (MOF) of the Atlantic Forest biome, is an important coniferous species in southern Brazil of considerable economic importance due to its exceptional wood quality and its high-value edible seeds (Hess et al, 2019, Costa et al, 2020. The species' trunk is highly cylindrical, straight and, rarely, branched into two or more shafts, its bark is thick and resinous, and it also has a unique crown structure (Narvaes et al, 2005;Rodrigues, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Due to unsustainable logging and agricultural expansion in past decades, MOF typology have experienced a significant reduction in its original area, culminating in the development of legal barriers for the cutting of Parana pine (Eisfeld et al, 2020). However, several researches have pointed out that these restrictions has not been effective to improve the state of conservation of the species (IUCN, 2021), since the the lack of management in this typology has led to a great increase in competition between trees, impeding natural regeneration and stagnating growth (Beckert et al, 2014;Costa et al, 2020;Hess et al, 2020Hess et al, , 2018aHess et al, , 2018b. Therefore, studies that contribute to the planning of sustainable forest management and conservation of this species are crucial.…”
Section: Introductionmentioning
confidence: 99%